Avalanches in 2D dislocation systems without applied stresses. (14th July 2015) - Janićević, Sanja; Ovaska, Markus; Alava, Mikko J; Laurson, Lasse
Abstract: We study avalanches in two-dimensional ensembles of discrete dislocations subject to zero or small finite constant external stresses. These systems respond to local perturbations by exhibiting bursts of collective dislocation activity characterised by power-law distributions of various measures of sizes and durations of the avalanches. The cut-offs of these distributions diverge with the system size even for zero applied stresses. The avalanches are found to display slow, glass-like relaxation dynamics following the initial excitation, with the average avalanche shape depending on the avalanche duration.